Capitals, capitalization, capitalism. Exploring the numerous faces of capital - Castien Maestro, Juan Ignacio (Cuadernos de Relaciones Laborales, 2013)
According to the marxian conception, capital represents a social mechanism that organizes and structures social relations characterised by domination and exploitation and it is defined as the social property which values adopt - objectified in money, productive forces or final products - when immersed in an appreciation process. This is a conversion process into capital which we call capitalization process. Traditional Marxism has tended to reduce the conditions of this process to the division between the owners of the means of production and the owners of their own labour power. However, there might be some other conditions that make it possible such as certain ’luxury wage-earners’, namely executives, highly qualified technicians, sportsmen and sportswomen of high level and prominent figures in show business who would be capitalizing their own labour power. We will try out a broader definition of the concept capital based on this and other kind of situations.